THE EFFECTIVENESS OF COUNSELING USING PUZZLE AND SNAKE AND LADDER GAME MEDIA ON DENTAL CARIES KNOWLEDGE IN ELEMENTARY SCHOOL STUDENTS - Mery Novaria Pay; Applonia Leu Obi; Melkisedek O. Nubatonis; Leny M. A. Pinat; Yansestina E. Eky (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background: Increasing knowledge can be done through dental health education efforts, namely counseling to provide information to the community. Efforts to increase knowledge can be given a stimulus through educational games to sharpen children's brains and make children creative because the world of children is a world of play. To support playing and learning activities, media is needed that can be interesting according to the characteristics of children's development. The aim of the study was to determine the effectiveness of counseling using puzzle game media and snakes and ladders on dental caries knowledge in elementary school students in Taebenu District. The research design uses a quasi-experimental research design with a non-equivalent control group design. Sampling was by purposive sampling, the instrument in the study used a questionnaire and the analysis used SPSS with the Wilcoxon and Mann-Whitney tests. The results of the study: there is a significant difference in the number of scores between the puzzle media game and the snakes and ladders media game. This is evidenced by the results of the Mann-Whitney test, which obtained a p-value of 0.000 <0.05. From the results of the study it was concluded that there was an increase in the level of knowledge of children who were given games using snakes and ladders media more effectively than children who were given games using puzzle media.